2001
DOI: 10.1055/s-2001-13588
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Surgery for Large Posterior Fossa Arachnoid Cysts

Abstract: The authors report two cases of large arachnoid cysts of the posterior fossa treated by endoscopic surgery. One patient underwent a successful endoscopic cyst fenestration by burr hole approach after several procedures of shunt revision. In another an endoscope-assisted microsurgical intervention was necessary. Lateral (cerebellar or cerebellopontine angle) cysts, as two reported cases, may be treated through a lateral retromastoid approach by fenestration into the prepontine cistern and eventually into the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…However, the effective treatment remains controversial, and there are reports in the literature highlighting this issue (3,6,12,14,18,21,24,26,29). These reports mostly concern the pediatric population, with the biggest series being reported by a European cooperative study that included 54 cysts at the posterior fossa from 17 institutions (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effective treatment remains controversial, and there are reports in the literature highlighting this issue (3,6,12,14,18,21,24,26,29). These reports mostly concern the pediatric population, with the biggest series being reported by a European cooperative study that included 54 cysts at the posterior fossa from 17 institutions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Less common presentations include ataxia, hearing loss, and facial nerve palsy (12,18,29). Hydrocephalus is considered very suggestive of the disease (6,8,14,19,28) and di Rocco et al found hydrocephalus in all of their eight patients with symptomatic PFAC (10). The association of other congenital anomalies is estimated to occur in 10 to 30% of cases (23,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Recently, advances in neuroendoscopic surgery have allowed treatment by endoscopic cyst fenestration. [3][4][5][7][8][9]14,16) Simple burr hole drainage has often been used in middle cranial fossa arachnoid cyst combined with subdural hematoma. However, various approaches have been selected in cases associated with subdural effusion.…”
Section: Discussionmentioning
confidence: 99%